BNT162b2 mRNA COVID-19 vaccine is safe in a setting of patients on biologic therapy with inflammatory bowel diseases: a monocentric real-life study. Issue 10 (3rd October 2022) - Pellegrino, Raffaele; Pellino, Gianluca; Selvaggi, Lucio; Selvaggi, Francesco; Federico, Alessandro; Romano, Marco; Gravina, Antonietta Gerarda
ABSTRACT: Objectives: Patients with inflammatory bowel disease were excluded from trials that led to the approval of anti-COVID-19 vaccines and are worthy of real-life studies providing information on the safety of these vaccines in this clinical setting. Methods: A prospective observational study was performed to estimate BNT162b2 mRNA COVID-19 Vaccine local and systemic adverse events (AEs) incidence related to administration in patients with inflammatory bowel disease through a questionnaire administered at the first, second, and third doses. Disease activity by Mayo Partial Score and Harvey-Bradshaw Index was also evaluated. Results: Eighty patients with a median age of 47.5 years were initially enrolled. The local AEs rate was 26.25%, 58.75%, and 28.37% at the first, second, and third doses of the vaccine, respectively. In contrast, the systemic AEs rate was 52.2%, 48.75%, and 43.24%. Clinic-demographic predictor variables for AEs were not identified. Vaccination did not affect disease activity and no statistically significant difference in disease activity index scores was observed between the three doses. No serious adverse events were observed. Conclusion: This vaccine was safe in a population of patients with inflammatory bowel disease and, therefore, could be safely administered in this clinical setting.